Criminal Profiling of Child Sexual Offenders: A Qualitative Case Study in Muaro Padang Class IIA Correctional Facility - Fikri, Harry Theozard; Rahmadani, Sari (Journal of Educational, Health and Community Psychology, 2025)
Sexual crimes against children are currently causing great concern in society due to the increasing number of reported cases. Many discussions related to sexual crimes against children focus on the victims, including the psychological impact and the victims' future survival, while the perpetrators have not been discussed in depth. Perpetrators of sexual crimes against children are a key aspect that requires in-depth analysis to comprehensively understand this phenomenon. This study aims to identify the profile of perpetrators of sexual crimes by analyzing their common traits and unique characteristics. The research design uses a qualitative study with a thematic analysis approach with constant comparison. Data were collected through interviews and documentation involving eight inmates from the Muaro Padang Class IIA Correctional Institution. Open observation and semi-structured in-depth interviews were conducted with subjects and informants to obtain detailed information. The findings highlight several key themes in criminal profiling, including: characteristics of perpetrators and victims, dynamics of the relationship between perpetrators and victims, sequence of criminal acts, patterns of victim selection, mechanisms of victim control, perpetrator motivations, and modus operandi. Overall, this study concludes that most perpetrators are young men; have a close relationship with the victim; have a pattern of grooming through promises, gifts, or threats; and the perpetrator's motive is dominated by the motive of sexual gratification. The results of this study have implications for the police to conduct more in-depth investigations; for parents and schools to take preventive measures; and for correctional institutions to provide appropriate psychological intervention for perpetrators.